Penyuluhan Perlindungan Perempuan dan Anak untuk Mewujudkan Ruang Aman di Desa Sendawar - Dipen Renaldy; Clara Intan Ramadhani; Oktavia Rahmadani; Dhaffa Hosya Putra; Nira Hayu Simbolon; Rila Bonita Siregar; Fadillah Nur Aziza; Hengki Gilang Kurniawan; Chelvin Agustion Saputra; Saprinurdin Saprinurdin (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
Women and children require protection from violence, discrimination, exploitation, and rights violations. This community service program aimed to improve Sendawar Village residents’ understanding of women’s and children’s rights, forms of violence, protection services, reporting mechanisms, and community roles in creating a safe environment. The program was conducted on July 20, 2026, at the Sendawar Village Office through a partnership involving Universitas Bengkulu students, the village government, and the Seluma Regency service unit for women and child protection. The activity involved 61 participants from village institutions, schools, youth groups, and the community. The stages included a pretest, material presentation, interactive discussion, question-and-answer session, and posttest using the same instrument. Descriptive analysis showed that the mean score increased from 40 to 80, representing an absolute gain of 40 points and a relative increase of 100 percent. The findings indicate improved short-term knowledge. Follow-up assistance and evaluation are needed to assess behavioral change and the sustainability of safe spaces.